THE CORRELATION OF LEFT VENTRICULAR MECHANICAL DISPERSION AND LEFT VENTRICULAR EJECTION FRACTION WITH QT DISPERSION IN END-STAGE RENAL DISEASE PATIENTS ON HEMODIALYSIS BEFORE AND AFTER DIALYSIS - Harry Pribadi; Agnes Lucia Panda; Benny Mulyanto Setiadi (JURNAL WIDYA MEDIKA, 2022)
Background: Ventricular arrhythmias (VA) is common in dialytic patients. Left Ventricular Mechanical Dispersion (LVMD) could provide an inhomogeneous of left ventricular myocardium contraction lead to VA. Reduced Left Ventricular Ejection Fraction (LVEF) and QT Dispersion (QTd) are well-known VA predictors in dialytic patients. This study aimed to determine the relationship between LVMD and LVEF on QT dispersion in ESRD patients before and after dialysis. Methods: This cross-sectional study was conducted in November 2021 - February 2022. All study subjects who met the inclusion criteria underwent history taking and physical examination including age, sex, body weight, body height, electrocardiography, echocardiography, and routine laboratory studies. Results: Among 43 subjects, 24 (55.8%) were male, with mean age of 51,14±11,6 was conducted in this study. The most common comorbidities were hypertension (79%) and diabetes mellitus (44.19%). Pre-dialysis LVMD mean was 28.99±15.98 ms and significantly decrease to 24.16±15.77 ms after dialysis (p